Selective Oxidation of Sulfides in Flow Chemistry; European Journal of Organic Chemistry; Vol. 2018, iss. 18 - Silva F. Filip; Baker A. Alastair; Stansall J. James; Michalska W. Weronika; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Graz M. Michael; Saunders R. Robert; Evans G. J. S. Gareth; Wirth Th. Thomas (2018, 2018)
Title screen